The innovations of idealism - Bubner, Rüdiger 1941-2007 (Modern European philosophy, 2003)
This collection of essays, first published in German in 1995, has been written by the foremost representative of the hermeneutical approach in German philosophy. It offers a quite original interpretation of the tradition of German Idealist thought - Kant, Fichte, Schelling, Hegel. Rüdiger Bubner seeks to cast fresh light on the genuine philosophical innovations in the complex of issues and aspirations which dominated German intellectual life from 1780 to 1830. His major question is: in what way did the Idealists change philosophy, reformulate traditional issues, and especially, reinterpret traditional figures? His answer to this question involves focusing on the literary and cultural spirit of the time, thus broadening the question of philosophical innovation and locating it within the wider framework of innovations and continuities within the Western intellectual tradition itself. This collection will be of special interest to students of German philosophy, literary theory and the history of ideas